The examination of Yo-Yo intermittent recovery test performance of young soccer players at different playing positions - Serdar Bayrakdaroğlu; Erdal Arı; Hüseyin Özkamçı; İbrahim Can (Physical Education of Students)
Background and Study Aim. The aerobic fitness in soccer is an important performance component. The aerobic endurance level of players may positively effect performance of critical match activities. The examination of Yo-Yo intermittent recovery test (YYIRT) performance of young soccer players at different playing positions was aimed in this study.